Reinforcing effects of phenethylamine analogs found in dietary supplements. - McGriff, Shelby A.; Chojnacki, Michael R.; Thorndike, Eric B.; Rice, Kenner C.; Baumann, Michael H.; Schindler, Charles W. (Psychopharmacology, 2022)
Rationale: Synthetic phenethylamine (PEA) analogs, such as β-methylphenethylamine (BMPEA) and N,α-diethylphenethylamine (DEPEA), are often found in dietary supplements, despite regulations prohibiting their sale. PEA analogs are structurally related to amphetamine, and we have shown that BMPEA and DEPEA produce cardiovascular stimulation mimicking the effects of amphetamine. However, few studies have examined behavioral effects of BMPEA, DEPEA, and other PEA analogs. Objectives: Here, we examined the reinforcing effects of α-ethylphenethylamine (AEPEA, 1 mg/kg/injection), DEPEA (1 mg/kg/injection), and BMPEA (3 mg/kg/injection) as compared to amphetamine (0.1 mg/kg/injection) using a fixed-ratio 1 self-administration paradigm in male rats. Methods: Male rats were trained in self-administration chambers containing 2 nose-poke holes. A nose-poke response in the active hole delivered drug or saline, whereas a nose-poke response in the inactive hole had no programmed consequence. Four groups of rats were initially trained for 10 days with the doses noted above. Upon acquisition of drug self-administration, a dose–effect function was determined by training rats on 3 additional doses for 3 days each. A separate group of rats was trained with saline. Results: Male rats self-administered each PEA analog and amphetamine, as shown by significant increases in active responses versus inactive responses. Subsequent dose–response testing showed clear differences in potency of the compounds. Amphetamine showed a typical inverted U-shaped dose–effect function, peaking at 0.1 mg/kg/injection. AEPEA and DEPEA also showed inverted dose–effect functions, with each peaking at 0.3 mg/kg/injection. BMPEA did not show an inverted U-shaped dose–effect function, but active responding slowly increased up to a dose of 6 mg/kg/injection. Conclusions: Taken together, our findings indicate that dietary supplements containing PEA analogs may have significant abuse liability when used recreationally.